Quem tem saudade da Escola Normal? - Marília Claret Geraes Duran; Jane Soares de Almeida (EccoS – Revista Científica)
Based on previous studies on teachers training for the early years of compulsory education, we emphasize in the article, some of the guiding principles and proposals which were articulated with the surroundings of the "Normal Course". The theme is developed considering three stages: the first affects set of the time, its uncertain path, the precarious ness of the first "normal schools" for graduating teachers in Brazilian territory. The second puts emphasis on issues of feminization of teaching and, thirdly, brand integration and equivalence of the "ordinary course" in all courses of the "school" with right of access to higher education, characterizing itself as vocational courses for primary teaching.